2
$\begingroup$

Right question, I am stuck. We have been working on matrices and I think I understand them, however I have no idea how to apply these to this transformation question.

Consider the points O = (0; 0; 0), A = (1; 3; 3) and B = (-2; -6; 4) together with the transformation which carries out a scaling to increase distances in the x direction by a factor of two, decrease those in the y - direction by a factor of three and leave distances in the z - direction unchanged. It also leaves the point A unchanged. What is the matrix associated with this transformation? Use the matrix to find the images of the following

(a) the point O
(b) the point A
(c) the point B
(d) the vector A->B
(e) the vector O->B
$\endgroup$
3
$\begingroup$

If the matrix you're looking for is a 3x3 matrix, then no such matrix exists, since

$A = x + 3y + z$, so $MA = Mx + 3My + 3Mz = (2,1,3) \neq A$.

But since you make the distinction between points and vectors, are you maybe working in projective space?

Then take the matrix $ N = \begin{bmatrix} 1 & 0 & 0 & A_x \\ 0 & 1 & 0 & A_y \\ 0 & 0 & 1 & A_z \\ 0 & 0 & 0 & 1 \\ \end{bmatrix} $

and let

$M = NSN^{-1}$,

where $S$ is the diagonal matrix with entries $(2,\frac{1}{3},1,1)$.

$\endgroup$
1
$\begingroup$

The above mentioned transformation can be written as an affine mapping in $R^3$: $$ \begin{bmatrix} x' \\ y' \\ z' \\ \end{bmatrix} = \begin{bmatrix} 2 & 0 & 0 \\ 0 & 1/3 & 0 \\ 0 & 0 & 1 \\ \end{bmatrix} \begin{bmatrix} x \\ y \\ z \\ \end{bmatrix} + \begin{bmatrix} -1 \\ 2 \\ 0 \\ \end{bmatrix} $$ It can also be written as a linear mapping in $R^4$ by introducing homogenous coordinates:

$$ \begin{bmatrix} x' \\ y' \\ z' \\ w' \end{bmatrix} = \begin{bmatrix} 2 & 0 & 0 & -1 \\ 0 & 1/3 & 0 & 2 \\ 0 & 0 & 1 & 0 \\ 0 & 0 & 0 & 1 \\ \end{bmatrix} \begin{bmatrix} x \\ y \\ z \\ 1 \end{bmatrix} $$

Using any one of these equations we get for the images (...)' of (...):

(a) O' = (-1, 2, 0)
(b) A' = (1, 3, 3) = A
(c) B' = (-5, 0, 4)
(d) (A -> B)' = B' - A' = (-6, -3, 1)
(e) (O -> B)' = B' - O' = (-4, -2, 4) 
$\endgroup$

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.